2020
DOI: 10.21077/ijf.2019.67.1.78466-06
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Biology of the Spiny Eel Macrognathus Pancalus Hamilton, 1822 From Upper Assam, India

Abstract: Reproductive biology of spiny eel Macrognathus pancalus Hamilton, 1822 was studied from the waterbodies of upper Assam, India. Sexual dimorphism was easily distinguished based on their body shape and colouration. Among the 467 fish samples examined, 312 males and 155 females were identified and the Male:Female (M:F) ratio ranged from 1:0.08 in November to 1:2.17 in June with overall sex ratio of 1:0.5. Five maturity stages were identified in a year and percentage distribution of each stage was calculated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 10 publications
3
12
0
Order By: Relevance
“…The present investigation indicated an annual synchronous breeding pattern in M. pancalus in the study area. Similar findings were also reported by Abujam and Biswas (2020) and Faridi et al (2020). Earlier studies by Abujam and Biswas (2020) revealed almost similar trends in GSI peak values in M. pancalus during May and June for males and females respectively.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The present investigation indicated an annual synchronous breeding pattern in M. pancalus in the study area. Similar findings were also reported by Abujam and Biswas (2020) and Faridi et al (2020). Earlier studies by Abujam and Biswas (2020) revealed almost similar trends in GSI peak values in M. pancalus during May and June for males and females respectively.…”
Section: Resultssupporting
confidence: 89%
“…It is a sturdy fish inhabiting a variety of habitats including 'beels'/wetlands, small rivers, streams, canals, inundated fields, river plains and estuaries of Pakistan, Nepal, Bangladesh and India (Rahman, 1989;Talwar and Jhingran, 1991;Galib et al 2009). The species commands considerable market value as both food and ornamental fish in domestic and international trade (Suresh et al 2006;Abujam and Biswas, 2011;Raghavan et al 2013). Their entire demands, however, are met through wild catches from their native habitats (Suresh et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Male dominancy over female may be due to accidental or natural mortality such as spawning stress of females in the population. reported by Abujam and Biswas (2011) and Kashyap et al (2016). However, it is worth mentioning here that several other workers (Qayyum and Qasim, 1964;Cardoso et al 2019) recorded the dominance of females over males.…”
Section: Discussionmentioning
confidence: 54%